Pengaruh Efktivitas Komunikasi Radiografer Pada Kepuasan Pasien di Instalasi Radiologi RS XYZ - Erwin; Edwin Suharlim; Evie Kusmiati; Intan Masita Hayati; Ria Andriyani (Jurnal Teknologika, 2025)
The effectiveness of communication is a crucial component in healthcare services, significantly contributing to patient satisfaction. In conventional contrast examination procedures, effective communication is essential for conveying information about the methods, benefits, risks, and preparation required for the examination. A survey conducted through interviews with 30 patients and their families at the Radiology Department of RS XYZ revealed that 23 respondents expressed dissatisfaction with the communication provided by radiology staff. They reported difficulties in understanding instructions and explanations, noted that explanations were poorly structured, some components were omitted prior to the examination, and the language used was often difficult to comprehend. This study aims to evaluate the effectiveness of radiographer communication in relation to patient satisfaction during conventional contrast examinations at RS XYZ. Employing a quantitative descriptive design with a survey method, data were collected via questionnaires distributed to 30 respondents undergoing conventional contrast examinations or their family members. The data were analyzed using the Percentage Index formula to measure satisfaction levels. The study was conducted between May and June 2025. Key factors assessed included respect, empathy, listening ability, clarity, and humility. The results showed that respect scored 68% (categorized as fairly satisfied), empathy 81% (satisfied), listening ability 88% (satisfied), clarity 85% (satisfied), and humility 75% (satisfied). The lowest score was for respect, while the highest was for listening ability. Overall, the effectiveness of radiographer communication in relation to patient satisfaction during conventional contrast examinations at RS XYZ reached 61%, categorized as satisfied.